Physics for scientists & engineers with modern physics - SERWAY, Raymond A. (Philadelphia : Saunders College Publishing, 1990)
This revised calculus-based physics text, has a problem solving approach, incorporating intermediate and challenging problems, spreadsheet problems, and conceptual problems with reasoning statements.
Includes index